Spectrophotometric methods for analysis of different dosage forms containing pyridoxine hydrochloride - Habib, Neven Magdy; Abdelwhab, Nada Sayed; Abdelrahman, Maha Mohamed; Ali, Nourudin Wageih (European Journal of Chemistry, 2016)
Two accurate, precise, sensitive and selective spectrophotometric methods have been developed and validated for determination of pyridoxine hydrochloride (PYH), cyclizine hydrochloride (CYH) and meclizine hydrochloride (MEH) either in their binary mixtures or in synthetic ternary mixtures. In modified area under the curve method (Method I), PYH has been determined by measuring amplitude value of the plateau at 283 nm (obtained after dividing the ternary mixture by standard spectrum of 20 µg/mL of PYH at which no interference from CYH and MEH) while area under the curve spectrophotometric method (AUC) has been used for calculating CYH and MEH concentrations in the ternary mixture by measuring the area under the curve in the range of 215-228 and 230-243 nm in the obtained division spectrum and after subtraction of the constant value at 283 nm. Method II is mean centering of ratio spectra spectrophotometric method (MCR) at which the mean centered ratio spectra in two successive steps have been used for measuring the amplitudes of the mean centered second ratio spectra amplitudes at 228.8, 262.0 and 270.8 nm for PYH, CYH and MEH, respectively. The proposed methods were successfully applied for determination of the cited drugs in their pharmaceutical formulations. Also they were statistically compared with the reported methods using student's-t and F-tests and there was no significant difference between them regarding both accuracy and precision.